Pengaruh Strategi Pembelajaran Takaku terhadap Penguasaan Konsep Mata Pelajaran Matematika Sekolah Dasar Kelas VI - M. Zainal Mustamiin; Muzakkir Muzakkir (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Learning strategy is one of the most important parts in the learning process so it is necessary for an education to determine the right strategy before the implementation of learning especially in mathematics learning which is believed to be difficult to understand makasimal The purpose of this study to find out the influence of the use of learning strategies takaku on the mastery of the concept of elementary school mathematics class VI B SDN Cakra Negara Mataram. Based on the graph, the average pretest values of 61 and postest 80 mean that there is a significant increase from before treatment and after treatment. Likewise, on the percentage there was a significant increase from before which was 45% and after being given treatment rose to 75%. This shows that there is an influence on the use of Takaku learning strategies on the mastering of concepts in mathematics subjects. In addition, the results of the calculation of research data that have been done are known sig values. 0,000 < 0.005 then Ho and Ha are accepted. This means that the use of Takaku startegi has an effect in increasing the mastery of the concept of mathematics subjects SDN Class B Cakra Negara in 2021/2022.